PENGARUH WORKLOAD, ORGANIZATIONAL JUSTICE, DAN WORK ENVIRONMENT TERHADAP KINERJA GURU SEKOLAH PAUD, TK, DAN SD DIBAWAH NAUNGAN AL-FURQON WILAYAH GABUS - rafizal; Heri Prabowo; Ratih Hesty Utami (STIE-PMCI, 2022)
This study aims to explain the effect of workload, organizational justice, and work environment on teacher performance (Case Study in PAUD, Kindergarten and Elementary Schools under the Al-Furqon Shade of the Gabus Region in 2022). This type of research is quantitative. The population in this study were PAUD, TK and SD school teachers under the Al-Furqon Shade of the Gabus Region. Data retrieval using questionnaire results sheets which were distributed to 80 respondents. Data collection techniques in this study used questionnaires and interviews with Multiple Linear Regression Analysis, with the help of SPSS software. The results of this study indicate that the t test has a negative effect on the workloadworkload (X1) on teacher performance, while organizational justice (X2) has a positive influence on teacher performance and work environment (X3) does not have a significant influence on teacher performance (Y). Based on this study that has been tested, there is an R Square value of 0.120 or 12%, while the remaining 0.880 or 88% is influenced by other variables that are not studied in this study.